Decomposing Differences in the First Moment - Myeong-Su Yun (Institute for the Study of Labor (IZA), 2003)
We propose a simple methodology for decomposing differences in the first moment into characteristics and coefficients effects. This methodology provides a way to apply the Blinder-Oaxaca decomposition to a non-linear function for both aggregate and detailed decompositions.
Keywords: C20; J70; 330; decomposition analysis; characteristics effect; coefficients effect; Dekompositionsverfahren; Lohndifferenzierung; Theorie